Analysis of Eddy Current: What Can Be Done to Reduce the Number of False Positives and False Negatives Made by Human Operators in Nondestructive Testing?. (September 2018) - Arbab, Yasmin; Nathan-Roberts, Dan
This work identifies the potential for improving the reliability of nondestructive testing (NDT) in the aviation industry. This particular work is focused on a piece of equipment called eddy current scanner and specifically investigates how this instrument, used to detect cracks on aircraft components, could be improved to better fit human needs and capabilities. Current research shows us that Type I and Type II errors, also known as false negatives and false positives, made by operators of the eddy current are in part due to workspace conditions, physical positioning, and mental states greatly affecting the amount of cognitive resources left available to perform a job accurately and reliably. Potential solutions that are within the realm of eddy current's design and possible enhancements are presented.